Profile of an occupation – electronics technician - Schambeck, Arne [Verfasser] (My University, 2025)
"Training to become an electronics technician is a future-proof option. Nowadays, everything which functions in a technological, electronic and automatic way contains a contribution from the skilled electrical trades. Electronics technicians are professionals in electrical appliances, in energy and building technology and in automation solutions. Trainees in this occupation can choose between two specialisms. This occupational profile describes the key tasks and presents current training figures." (author's abstract; BIBB-Doku)
Keywords: S 6.2.4 Elektroberufe; 370; Elektroniker für Automatisierungs- und Systemtechnik; Elektroniker für Energie- und Gebäudetechnik; Tätigkeitsmerkmal; Beurfsbild